How does managerial cognition affect the speed of internationalization? - Santos, Inês Grijó Pinto de Almeida (2021)
This research explores the influence of the decision-making process on the internationalization, specifically the speed of internationalization process. The objective of this study consists in perceiving the influence of managerial cognition through the process of decision-making (perception, options, evaluation and final choice) on small ventures’ speed of internationalization. The managerial cognition is investigated at the light of the Dual-Process Theory, that consists in the existence of two cognitive systems, the experiential cognitive system (System 1) and the analytic cognitive system (System 2). The speed of internationalization is analyzed through two different dimensions, earliness or speed of pre-internationalization and acceleration or speed of post-internationalization. Grounded upon interviews with five managers of international small ventures, it was found that companies that internationalize earlier are managed by decision-makers who have higher levels of experiential cognitive reasoning during the first and subsequent internationalizations while companies that internationalize later are managed by decision-makers who have higher levels of analytic cognitive reasoning during the first and subsequent internationalizations. International experience was found to influence the acceleration of companies.